A revision of male ants of the Malagasy region (Hymenoptera: Formicidae): Key to subfamilies and treatment of the genera of Ponerinae - Yoshimura, Masashi; Fisher, Brian L. (Zootaxa, 2007)
Male-based keys to ant subfamilies and to the genera of Ponerinae in the Malagasy region (Madagascar, Mauritius, Reunion, Comores, and Seychelles) are presented. Seven subfamilies known from the Malagasy region in addition to an undetermined taxon are included in the subfamily key. All seven of the ponerine genera recorded in the region—Anochetus, Hypoponera, Leptogenys, Odontomachus, Pachycondyla, Platythyrea, and Ponera—are included. Diagnoses and remarks on the subfamily and genera within Ponerinae, and a character table for the ponerine genera, are given. The males of the seven ponerine genera are illustrated.